Credit, income and inequality - Manthos D. Deles; Fulvia Fringuellotti; Steven Ongena (Federal Reserve Bank of New York, 2020)
Analyzing unique data on loan applications by individuals who are majority owners of small firms, we detail how a bank's credit decisions affect their future income. We use the bank's cutoff rule, which is based on the applicants' credit scores, as the discontinuous locus providing exogenous variation in the decision to grant loans. We show that application acceptance increases recipients' income five years later by more than 10 percent compared to denied applicants. This effect is mostly driven by the use of borrowed funds to undertake investments, and is stronger when individuals are more credit-constrained.
Keywords: D31; E24; G21; O15; 330; credit constraints; income; business loans; economic mobility; income inequality; regression discontinuity design